1993
DOI: 10.1002/ajmg.1320470540
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive skills in achondroplasia

Abstract: Increased intracranial pressure and ventricular and subarachnoidal dilatation are common manifestations in achondroplasia. They rarely lead to major neurologic and/or psychomotor deficits and neurosurgical intervention is seldom needed. The present study was undertaken to detect signs of minor cerebral dysfunction and discuss possibilities of their prevention. Thirty children with achondroplasia were compared to 3 control groups: their next-born sibs, 30 children with other forms of dwarfism, and 30 children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 15 publications
1
27
1
Order By: Relevance
“…Yet, the influence of hydrocephalus on cognitive development in ACH is not clear. Although intelligence has been described as normal in ACH, cognitive deficits have been reported [Brinkman et al, 1993]. Brinkman et al [1993] studied a group of 30 children with ACH in comparison to children with other forms of dwarfism, sibling controls, and normal controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the influence of hydrocephalus on cognitive development in ACH is not clear. Although intelligence has been described as normal in ACH, cognitive deficits have been reported [Brinkman et al, 1993]. Brinkman et al [1993] studied a group of 30 children with ACH in comparison to children with other forms of dwarfism, sibling controls, and normal controls.…”
Section: Introductionmentioning
confidence: 99%
“…Although intelligence has been described as normal in ACH, cognitive deficits have been reported [Brinkman et al, 1993]. Brinkman et al [1993] studied a group of 30 children with ACH in comparison to children with other forms of dwarfism, sibling controls, and normal controls. They found that children with ACH had more frequent histories of early motor and speech development delay and lower school grades.…”
Section: Introductionmentioning
confidence: 99%
“…In adults, lumbar spinal stenosis leads to cauda equina syndrome of varying degrees of severity. Short, small eustachian tubes lead to an increased incidence of otitis media and hearing problems [Brinkmann et al, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…Sporadic cases of achondroplasia and other dominant genetic disorders have been associated with advanced paternal age, suggesting that these mutations occur preferentially during spermatogenesis [9,10]. Diagnosis of achondroplasia is based on clinical findings, radiographic features and genetic test results [11]. In our study, all cases were disproportionately short with short limbs mainly proximal (rhizomelic); they had relatively long narrow trunk.…”
Section: Discussionmentioning
confidence: 52%